A methodology to integrate solar thermal energy in district heating networks confronted with a Swedish real case study. (September 2017) - Joly, Martin; Ruiz, Gabriel; Mauthner, Franz; Bourdoukan, Paul; Emery, Morgane; Anderson, Martin
Abstract: Among other solutions, the integration of solar energy in district heating networks can contribute significantly to the increase of the renewable energy fraction in an urban area. This article describes the methodology developed in the framework of IEA Task 52 to help stakeholders during early phases of new or refurbishments projects. This methodology integrates a tool which is capable to assess the main solar indicators of the project with only two inputs: the solar installation area and the building heated area. The tool outputs are compared to the measured values of a Swedish case study.